Who is American? A comprehensive analysis of the American = White/Foreign = Asian stereotype (2007–2023) - Kirsten N. Morehouse; Tessa E. S. Charlesworth; Thierry Devos; Mahzarin R. Banaji (Scientific Reports)
Abstract Against the backdrop of increasing ethnic diversity in the U.S., we replicate, extend, and challenge previous examinations of the American = White/Foreign = Asian stereotype in the largest sample to date (N = 666,623 respondents) over 17 years (2007–2023). Six key findings emerged. First, a robust American = White association emerged on implicit (Cohen’s d = 0.50) and explicit (Cohen’s d = 0.51) measures. Second, the strength of this effect varied by respondents’ race/ethnicity with implicit stereotypes strongest among White respondents (Cohen’s d = 0.86) and absent among East Asian respondents (Cohen’s d = 0.02). Third, the strength of implicit stereotypes was modulated by age, religion, and ideology—older, Christian, and conservative respondents displayed stronger implicit American = White associations—but not gender or education. Fourth, respondents living in U.S. metropolitan areas with greater Asian representation or a history of voting for Democratic candidates exhibited weaker implicit American = White associations. Fifth, over the past 17 years, implicit and explicit American = White associations decreased by 41% and 47%, respectively, and 14/14 demographic subgroups changed towards neutrality. Finally, we observed suggestive evidence that implicit stereotype trends towards neutrality were temporarily disrupted during the COVID-19 pandemic for White Americans but not Asian Americans.